2015
DOI: 10.1016/j.amepre.2015.07.021
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Impact of Juvenile Curfew Laws on Public Health and Justice Outcomes

Abstract: Context Automobile crashes cause more than 800,000 youth injuries and deaths each year. Other youth suffer the consequences from being either a perpetrator or victim of a crime. One type of law that has an effect on youth behavior is juvenile curfew laws. These laws restrict the times that youth may occupy public places or streets. We systematically reviewed studies evaluating the effectiveness of these laws to address the question: Can juvenile curfew laws be used to improve youth public health and juvenile j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Elyse et al and Shatz et al stated that curfew restriction had a positive effect on juvenile traumas (Grossman, & Miller., 2015;Shatz, et al, 1999). From the pediatric age group, only the trauma patients admitted to the emergency department at Sakarya University Training and Research Hospital.…”
Section: Resultsmentioning
confidence: 99%
“…Elyse et al and Shatz et al stated that curfew restriction had a positive effect on juvenile traumas (Grossman, & Miller., 2015;Shatz, et al, 1999). From the pediatric age group, only the trauma patients admitted to the emergency department at Sakarya University Training and Research Hospital.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, some studies have shown that curfews do lead to an increase in juvenile crimes (Adams 2003). A recent systematic review of the effects of curfews on juvenile crime and victimization found only eight studies, four of which reported a positive impact (Grossman and Miller 2015). Despite that positive finding, the authors concluded that, given the state of research, the number of studies and their quality means that more research is needed before drawing firm conclusions about the effectiveness of juvenile curfew laws.…”
Section: Curfewsmentioning
confidence: 99%
“…For example, they have ignored other related factors such as zero tolerance laws, measures to reduce gang activity, and poverty rates that may influence the impact of curfew laws when outcomes are simply reductions in crime or victimization. Perhaps even more problematic, no studies have examined the extent to which curfew laws actually are enforced; they focus, instead, on the presence of laws (see, again, Grossman and Miller 2015).…”
Section: Curfewsmentioning
confidence: 99%
“…The relationship between juvenile curfews and crime and victimization do not reveal promising results (Petersilia, 1986; Adams, 2003; Bonta, Wallace-Capretta, & Rooney, 2000a). Grossman and Miller’s (2015) systematic review of eight curfew studies since 1999 found only half of the studies identified an impact of curfews on juvenile crime. In their review, the authors called for more “rigorous research” on this topic as the studies in their analysis were fraught with methodological issues ranging from no covariates, self-report criminal activity, and use of nonnationally representative panel data (Grossman & Miller, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Grossman and Miller’s (2015) systematic review of eight curfew studies since 1999 found only half of the studies identified an impact of curfews on juvenile crime. In their review, the authors called for more “rigorous research” on this topic as the studies in their analysis were fraught with methodological issues ranging from no covariates, self-report criminal activity, and use of nonnationally representative panel data (Grossman & Miller, 2015). The following year, in 2016, the Campbell Collaboration, published its own systematic review on the effects of juvenile curfew on crime and victimization (Wilson, Gill, Olaghere, & McClure, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%